Does participation lead to empowerment? : the case of women potato farmers in Pakistan - Amjad (Curtin University, 2014)
Pakistan is a developing country with the majority of the people living in rural areas and dependent on the agricultural sector for their livelihood. Women constitute more than half of the rural population, thus should be included in developmental strategies for rural areas. This requires understanding of their participation in economic activities. This research project attempts to measure the current level of participation of women potato farmers and its impact on income and empowerment.